Effect of ultrasound combined with microbubbles therapy on tumor hypoxic microenvironment - Yuyi Feng; Danxia Qiu; Yangcheng He; Hai Jin; Liping Chen; Fen Xi; Zhiwen Hu; Yanlin Xie; Yucai Li; Minhua Lin; Pengxiao Sun; Yan He; et al. (Frontiers in Pharmacology)
IntroductionTumor tissues exhibit significantly lower oxygen partial pressure compared to normal tissues, leading to hypoxia in the tumor microenvironment and result in resistance to tumor treatments. Strategies to mitigate hypoxia include enhancing blood perfusion and oxygen supply, for example,by decomposing hydrogen peroxide within the tumor. Improving hypoxia in the tumor microenvironment could potentially improve the efficacy of cancer treatments. Previous studies have demonstrated that ultrasound of appropriate intensity when combined with microbubbles, can improve tumor blood perfusion. However, its effects on tumor hypoxia remain unclear. This study aimed to assess the effects of low-frequency non-focused ultrasound combined with microbubbles at different intensities on tumor microenvironment hypoxia and to identify the optimal ultrasound parameters for alleviating tumor hypoxia.MethodRabbits with VX2 tumors received ultrasound and microbubble treatments at different acoustic pressures and pulse repetition frequencies. The changes in tumor tissue blood perfusion before and after treatment were observed by contrast enhanced ultrasound (CEUS). The changes in tumor tissue hypoxia before and after treatment were observed by measuring oxygen partial pressure directly with in tumor tissue and immunohistochemical staining for hypoxia-inducible factor-1α (HIF-1α).ResultsResults indicated that low frequency, non-focused ultrasound at 0.5 MPa/20 Hz and 0.5 MPa/40 Hz, when combined with microbubbles, could increase tumor tissue blood perfusion and improve the hypoxia in tumor tissues.DiscussionThis study provides a new method for improving hypoxia in the tumor microenvironment (TME) which could potentially improve the cancer treatments resistance.